2022
DOI: 10.3389/fmicb.2022.791110
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacterial Inoculant Delivery Methods for Cereal Crops

Abstract: Despite growing evidence that plant growth-promoting bacteria can be used to improve crop vigor, a comparison of the different methods of delivery to determine which is optimal has not been published. An optimal inoculation method ensures that the inoculant colonizes the host plant so that its potential for plant growth-promotion is fully evaluated. The objective of this study was to compare the efficacy of three seed coating methods, seedling priming, and soil drench for delivering three bacterial inoculants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Thus, in the present study, techniques were applied to identify bacterial isolates with an important role in the construction of an inoculant consortium to be implemented in the I. cangae preservation, according to Chai et al [ 87 ] and Olanrewaju and Babalola [ 88 ]. In addition, the activities presented by the bacterial isolates deserve to be investigated from the perspective of biotechnology resources.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present study, techniques were applied to identify bacterial isolates with an important role in the construction of an inoculant consortium to be implemented in the I. cangae preservation, according to Chai et al [ 87 ] and Olanrewaju and Babalola [ 88 ]. In addition, the activities presented by the bacterial isolates deserve to be investigated from the perspective of biotechnology resources.…”
Section: Discussionmentioning
confidence: 99%
“…This points out the importance of implementing different inoculation methods into experimental designs and to the need of comparing multiple inoculation methods when studying plant-microbe interactions. A recent study on sorghum (Sorghum bicolor) also showed that inoculation practices impacted the total abundance of different bacterial species at an earlier harvesting point, but not at a later harvesting point (Chai et al 2022).…”
Section: Inoculation Practices Affect Microbial Communitiesmentioning
confidence: 98%
“…Seed coating, seed priming, root colonization, foliar application, and soil drenching are the popular methods of microbial inoculation. Chai et al (2022) observed that prolonged seed coating could efficiently boost the colonization of the endophytic bacterium C. pinensis in cereal crops [93]. On the contrary, Inoculation of Ochrobactrum spp.…”
Section: Phytomicrobiome and Pesticide Biodegradationmentioning
confidence: 99%